2023
DOI: 10.1155/2023/6837797
|View full text |Cite
|
Sign up to set email alerts
|

Study on Salmonella Isolates from Fresh Milk of Dairy Cows in Selected Districts of Wolaita Zone, Southern Ethiopia

Abstract: Salmonella infections are most commonly found in animal-derived foods. From December 2021 to May 2022, the researchers conducted a cross-sectional study to determine the prevalence of Salmonella isolated from raw milk collected in and around Areka town, Boloso Sore Woreda, Wolaita Zone, Southern Ethiopia. A total of 151 direct udder milk samples were collected at random and examined using bacteriological methods. The overall prevalence of Salmonella was 9.3% (14/151). Breed, age, body condition, lactation stag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 30 publications
0
1
1
Order By: Relevance
“…Unlike the ndings of our study, a higher incidence of Salmonella spp were shows up in Wolaita, SNNPR, Ethiopia that revealed 9.3% among 151 raw milk samples 44 , in this region also another study showed that 8.3% occurrence of Salmonella species from 384 raw milk samples, they use also 45 .…”
Section: Discussioncontrasting
confidence: 92%
“…Unlike the ndings of our study, a higher incidence of Salmonella spp were shows up in Wolaita, SNNPR, Ethiopia that revealed 9.3% among 151 raw milk samples 44 , in this region also another study showed that 8.3% occurrence of Salmonella species from 384 raw milk samples, they use also 45 .…”
Section: Discussioncontrasting
confidence: 92%
“…Based on the parent’s response to the risk exposures, boiled or pasteurized milk reported to have been used by the household members including the ill child, two weeks prior to the onset of the diarrhea. Milk is reported among the potential source of Salmonella in many settings ( Maichin et al, 2013 ; Lubote et al, 2014 ; Silva et al, 2014 ; ElBaz et al, 2017 ; Asefa et al, 2023 ). Additionally, ST166 was detected in tap water from the street adjacent to the residence of the case linked with ST166.…”
Section: Discussionmentioning
confidence: 99%